Are Some Countries More Honest than Others? Evidence from a Tax Compliance Experiment in Sweden and Italy - Andrighetto, Giulia; Zhang, Nan; Ottone, Stefania; Ponzano, Ferruccio; D'Attoma, John; Steinmo, Sven (Frontiers in Psychology, 2016)
This study examines cultural differences in ordinary dishonesty between Italy and Sweden, two countries with different reputations for trustworthiness and probity. Exploiting a set of cross-cultural tax compliance experiments, we find that the average level of tax evasion (as a measure of ordinary dishonesty) does not differ significantly between Swedes and Italians. However, we also uncover differences in national “styles” of dishonesty. Specifically, while Swedes are more likely to be either completely honest or completely dishonest in their fiscal declarations, Italians are more prone to fudging (i.e., cheating by a small amount). We discuss the implications of these findings for the evolution and enforcement of honesty norms.